STRATEGI PENGEMBANGAN USAHA JAKET KULIT “INTAN JAYA MANDIRI” KOTA BEKASI: BUSINESS DEVELOPMENT STRATEGIES LEATHER JACKET “INTAN JAYA MANDIRI” BEKASI CITY - Budiyono, Haris; Ardisela, Dawud; Rahman, Dasep Abdul (Fakultas Pertanian Universitas Islam 45 (UNISMA) Bekasi, 2023)
Intan Jaya Mandiri (IJM) The leather jacket is one manufacturer that produces of leather jacket. This study aims to identify the internal factors (strengths and weaknesses), identifying external factors (opportunities and threats) and formulate alternative strategy of business development. The analysis tool uses a matrix of IFE, EFE, IE, and SWOT Based on the result of the research, the total IFE score is 2,569, while the total value of EFE is 2.592. This effort is in quadrant V (maintain and maintain). Alternative strategies that can be run to expand marketing by promoting products, offering product designs/models, maintaining prices, diversifying products, improving product quality, benchmarking of successful companies in the leather industry, strengthening banking confidence, strengthening organizations and human resources. The main priority strategy based on the result is to expand marketing and promote products using social media with Summary Total Attractiveness Score (STAS) 4,039.